Key4hep: Progress Report on Integrations - Brondolin Erica; Carceller Juan Miguel; Deconinck Wouter; Fang Wenxing; Francois Brieuc; Gaede Frank-Dieter; Ganis Gerardo; Hegner Benedikt; Helsens Clement; Huang Xingtao; Joosten Sylvester; Ko Sang Hyun; et al. (EPJ Web of Conferences, 2024)
Detector studies for future experiments rely on advanced software tools to estimate performance and optimize their design and technology choices. The Key4hep project provides a flexible turnkey solution for the full experiment life-cycle based on established community tools such as ROOT, Geant4, DD4hep, Gaudi, podio and spack. Members of the CEPC, CLIC, EIC, FCC, and ILC communities have joined to develop this framework and have merged, or are in the progress of merging, their respective software environments into the Key4hep stack. These proceedings will give an overview over the recent progress in the Key4hep project: covering the developments towards adaptation of state-of-theart tools for simulation (DD4hep, Gaussino), track and calorimeter reconstruction (ACTS, CLUE), particle flow (PandoraPFA), analysis via RDataFrame, and visualization with Phoenix, as well as tools for testing and validation.